The Borrowing and Monitoring Medical Equipment Application in Hospital and Laboratory - Pradana, Yudha (Medika Teknika : Jurnal Teknik Elektromedik Indonesia, 2024)
Good management of medical equipment in hospitals is mandatory, with the aim of ensuring that it is always well monitored. The management of this medical equipment is usually done manually by filling in forms and assisted by word and number processing software carried out by electromedical staff. With so many medical devices in hospitals and so few electromedical personnel, plus data collection is still carried out manually,  it will not be easy to find information on the management of these devices, and it will take a long time. Research on Borrowing and Monitoring Medical Devices in Hospital and Laboratory Applications is a web application that was built using  PHP  and  XAMPP  coding as a database. This application aims to make it easier for users to borrow and monitor medical equipment in hospitals and laboratories. In this application, users can borrow medical equipment online and monitor the condition of the borrowed medical equipment. Apart from that, this application is also equipped with a notification feature to remind users about the due date for returning borrowed medical equipment. Hopefully, this application can increase efficiency and effectiveness in managing medical equipment in hospitals and laboratories.